Correlation of Placental Thickness with Biparietal Diameter in Normal Singleton Pregnancy among Bangladeshi Women (IAHS Medical Journal, 2026)
Background: Accurate estimation of Gestational Age (GA) is crucial for effective antenatal care. While the first day of the Last Normal Menstrual Period (LNMP) is commonly used when menstrual cycles are regular, alternative methods are needed in certain situations. Placental Thickness (PT) has been reported in various countries as a reliable ultrasonographic parameter for GA estimation. This study aimed to assess the relationship between PT and conventional fetal biometric measurements to evaluate its usefulness in estimating GA. To measure and assess placental thickness as an ultrasonographic parameter for estimating gestational age in uncomplicated pregnancies in Chattogram, Bangladesh.Materials and methods: A cross-sectional observational study was carried out among 112 healthy pregnant women between 11 and 40 weeks of gestation. Participants with no medical complications were recruited from the Radiology and Imaging departments of Chittagong Medical College Hospital and Islami Bank Hospital Agrabad, Chattogram. The study population was categorized into three gestational groups: 11–13 weeks, 14–26 weeks and 27–40 weeks.Results: Placental thickness was found to increase progressively with Biparietal Diameter (BPD) as gestational age advanced. At 12–13 weeks, there was a moderately strong positive correlation between PT and BPD. During 14–26 weeks, the correlation remained statistically significant but mild, while a weaker yet significant positive correlation was observed between 27–38 weeks of gestation.Conclusion: The findings indicate that placental thickness increases steadily with gestational age and can serve as a reliable ultrasonographic biometric parameter for estimating gestational age in normal pregnancies.IAHS Medical Journal Vol 8(2), December 2025; 67-70